Criminal sanctions for murder with necrophilia (case study 519/PID.B/2021/PN.JKT.PST) - Rymundus Loin; Budimansyah Budimansyah; Warriyodi Warriyodi (Journal of Law Science, 2024)
Today's rapes typically involve murder, and criminals have sexual relations with corpses. This research asks: how are criminal consequences for murderers who have sexual contact with a body related to the Central Jakarta District Court Decision Number 519/Pid.B/2021/PN.Jkt.Pst? How should the victim's family handle the judge's sentencing for murder with sexual contact with a corpse? This research uses normative juridical legal research. Secondary data informs normative legal research. Primary, secondary, and tertiary legal materials provide secondary data. The research found that the public prosecutor's indictment does not require legal regulation of murder accompanied by sexual intercourse with a corpse because it is difficult to charge perpetrators of rape of corpses with the Criminal Code and there are no articles that explicitly regulate sexual intercourse/rape (creating a legal vacuum). Indonesian law does not yet define corpse rape/sexual intercourse. Sexually interacting with a corpse is not rape. The Central Jakarta District Court Decision Number 519/Pid.B/2021/PN Jkt.Pst. addresses murder with sexual contact with a corpse. The author believes the perpetrator's punishment has not deterred the crime and has not satisfied the victim's family and society. The victim's family can ask the judges to sentence the defendant to the death penalty because the actions were cruel, barbaric, and inhumane. This is hoped to give the family a sense of justice and have an impact. prevention for criminals.